Ornithine carbamoyltransferase genes and phaseolotoxin immunity in Pseudomonas syringae pv. phaseolicola - Peet, Richard C. (1987)
Two different DNA fragments encoding ornithine carbamoyltransferase (OCTase) were cloned from Pseudomonas syringae pv. phaseolicola NPS3121. These fragments did not cross-hybridize and encoded OCTases which differed with respect to their sensitivity to purified phaseolotoxin, an OCTase inhibitor produced by this phytopathogenic bacterium. Recombinant plasmids carrying these DNA fragments complemented OCTase-deficient strains of Escherichia coli and Pseudomonas aeruginosa. Extracts of the complemented E. coli strain contained OCTase enzyme activities with similar degrees of sensitivity to purified phaseolotoxin as extracts of P.s.phaseolicola grown at either 20 or 30°C. The OCTase activity detectable in extracts of P.s.phaseolicola grown at 20°C is insensitive to phaseolotoxin while that detectable in extracts of cells grown at 30°C is sensitive to the toxin. E.coli HB101 harboring recombinant plasmids carrying the gene(s) encoding the phaseolotoxin-insensitive enzyme activity exhibited resistance to purified phaseolotoxin. The results of Tn5 mutagenesis and Southern blotting and the pattern of complementation of OCTase-deficient and Tox(-) mutant strains suggest that the gene(s) encoding the phaseolotoxin-insensitive OCTase is part of a gene cluster involved in phaseolotoxin production.